Liriomyza huidobrensis (Blanchard) LIFE CYCLE, HABITS AND NATURAL ENEMIES IN BULB ONION (Allium Cepa L.) - HINCAPIÉ-C., MARÍA CRISTINA; SAAVEDRA-H., MARÍA EUGENIA; TRÓCHEZ-P., ADOLFO LEÓN (Revista Colombiana de Entomología, 1993)
The present study on the life cycle, damage evaluation and natural enemies of the leafminer Liriomyza huidobrensis (Blanchard) in cultivated bulb onion was conducted at the ICA'S Plant Protection laboratory in Palmira (Colombia), at 1006 masl, the average temperature of 24.7C and relative humidity of 64.3%, and the site of Rozo in Palmira, and the towns of Yumbo and El Cerrito (Valle del Cauca). The average duration of the egg was 1.5 days; larva 5.54 days; prepupa 4 hours 2 minutes and pupa 8.14 days; the longevity of the female adult was 15 days and that of the male 7.6 days; the number of eggs per female was 100; the sex relationship was 1.42 9?: The behavior of the insect during their active stages was also determined and some particularities of the feeding habits of the larvae and adults were found. The population fluctuation was measured by the use of insects traps, showing a high density at the Auji site in El Cerrito (maximum of 6137 and mínimum of 1664 adults/900 cm2), while in Rozo, Municipality of Palmira, the population was low (maximum of 242 and minimum of the 8 adults/900 cm2). The most used insecticides in the area of the study were abamectin and cyfluthrin. As natural enemies were found three parasitic Hymenoptera: Diglyphus sp. (Eulophidae), Halticoptera sp. (Pteromalidae), and possibly Opius sp. (Braconidae). Plants found as hosts of L. huidobrensis were: beans (Phaseolus vulgaris), kindney beans (P.vulgaris var. humilis), cucumber (Cucumis sativus), cabbage (Brassica oleracea), garlic (Allium sativum), chrysanthemum (Chrysanthemum sp), red tasselflower (Emilia sonchifolia), galinsoga (Galinsoga parviflora), prickly sow-thistle (Sonchus asper), pigweed (Amaranthus retroflexus), pusley (Portulaca oleracea), umbrella (Hydrocotile umbellata) y burnweed (Datura stramonium).